Implementation of Village Land Utilization Policy in Bantul Regency - Farida Khasanah, Nor; Laksamana, Rofiq; Rahmanto, Nur; Nashih Luthfi, Ahmad; Salim, M. Nazir (Sekolah Tinggi Pertanahan Nasional, 2023)
The Special Region of Yogyakarta has experienced developments (or can also be termed as